Dramaturgi Performance Team Vokal Grup Metal Ensembel Tikoro - Anggita Lestari; Faisal Reza; Hilman Mulyadi; Nugraha Sugiarta; Yanuar Ilham (ArtComm, 2024)
This research is titled “Dramaturgy of the Vocal Group Metal Ensemble Tikoro.” Dramaturgy is a concept that examines the complex roles of individuals in everyday life, especially when performing on stage, which has both front and back stages. This study aims to understand the reality that occurs on the front and back stages of Ensemble Tikoro vocal group members, as well as to uncover how each member presents themselves. The research method used is qualitative with a dramaturgical concept approach. The research subjects involve all members of the Ensemble Tikoro. Data was collected through in-depth interviews, observations, and documentation. The data validity test used is source triangulation. The results of this study reveal that on the front stage, Ensemble Tikoro members perform with unique characteristics, namely wearing all-black costumes from head to toe. On the back stage, Ensemble Tikoro members interact with family and other activities using Sundanese and Indonesian languages, creating a familiar atmosphere. In self-presentation, Ensemble Tikoro members naturally express themselves through the choice of black costumes that become their identity. Thus, this research reveals the dynamics between the realities on stage and backstage of Ensemble Tikoro members, as well as how they radiate self-presentation through elements such as costumes and language they use.